II. Meşrutiyet döneminde Darülfünun - (:unkn) unknown (My University, 2008)
0

The idea of creatin a Darülfünun (university) in Turkey was born in the second half of the 19th century. Yet, the three ‘universities’ that opened one after another during this period were short lived. The Darülfünun-i Şahane (Imperial University) that opened in 1900 was, however, more institutionalized from the begining. It embodied three schools: the first for ‘Mathematical and Natural Sciences’, and the others for ‘Religious Sciences’, and ‘Literature’. Following the proclamation of a Constitution in 1908, the ‘Committee for Union and Progress’ undertook the reorganisation of the university. Emrullah Efendi, the Minister of Education, played an important role in this project. The year 1909 saw a number of institutional changes at the Darülfünun: the School of Law became part of the University, while the military and civilian medical schools were unified and integrated in the university, as well. Although attempts to issue regulations proved unfruitful, the educational system (the curriculum, examinations etc.) was recast and the academic hierarchy was established in 1913. In 1916, the medical faculty was endowed with a special regulation allowing the school to function rather independently. During WWI, some 20 scholars from Germany were invited to teach in the the faculties of Science, Literature and Law. Due to war circumstances and for various other special reasons, this reorganisation did not have longlasting effects in every field. The Reform in chemical education proved relatively more successful. Regulations for the university could only be issued in 1919 when this institution was given a new legal status allowing for autonomy in administrative and financial matters.
İstanbul Darülfünunu ( University ) in the aftermath of the young Turk revolution
Keywords: Tarih